Perbedaan Kematangan Pedagogical Content Knowledge Guru IPA Berdasarkan Gender dan Masa Mengabdi - Nevrita Nevrita; Nurul Asikin; Bony Irawan (Department of Biology Education, Faculty of Education and teacher Training, Maritime University of Raja Ali Haji, 2021)
TPACK maturity is an important quality of a modern professional teacher, especially in the current state of the pandemic which requires certain level of technological mastery from teachers. There remain questions as to what variables contributed to TPACK maturity of teachers. The research objective was to examine TPACK maturity among teachers along different tenure lengths and gender. The research was conducted in Tanjungpinang City with a sample of 32 science junior high school teachers consisting of 26 female teachers and 6 male teachers. Data was collected through a questionnaire, assessing 7 aspects of teacher’s TPACK. The results show that teachers with less than 12 years tenure length scored higher in TPACK maturity than teachers with 12 to 24 years tenure length, while teachers with more than 24 years tenure length score the lowest. We suggest this result is moderated by the age group variables from the samples. Based on genders, there is no significant difference in TPACK maturity between male teachers and female teachers. The conclusion is that there are differences in the teacher’s TPACK maturity based on tenure lengths, but there is no significant difference based on gender.